1979
DOI: 10.1177/0148607179003006433
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition utilization: evaluation of an educational protocol and consult service

Abstract: A two part study was undertaken to evaluate the effectiveness of an educational protocol and consult service on parenteral nutrition (PN) utilization. Forty-one patient admissions were evaluated retrospectively and nine prospectively. Average length of hospital stay and number of days on PN were decreased significantly (p less than .05). Frequency of adverse effects were also decreased significantly (p less than .05). A positive trend toward selection of patients for enteral rather than PN was evidenced. Utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
2

Year Published

1981
1981
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 0 publications
0
48
2
Order By: Relevance
“…Although previous studies have shown reductions in the incidence of metabolic complications [4,5], our study failed to show significant differences in the number of metabolic abnormalities among the different groups. This inability to demonstrate a significant effect of the NSS most likely reflects the fact that both the percentage of abnormal tests/patient/TPN day and the overall group sizes were small.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have shown reductions in the incidence of metabolic complications [4,5], our study failed to show significant differences in the number of metabolic abnormalities among the different groups. This inability to demonstrate a significant effect of the NSS most likely reflects the fact that both the percentage of abnormal tests/patient/TPN day and the overall group sizes were small.…”
Section: Discussioncontrasting
confidence: 99%
“…Hickey and colleagues combined mechanical and metabolic complications to show a significant reduction in "adverse reactions" [5]. The present study did not demonstrate a significant reduction in mechanical complications, which were limited to pneumothorax and subclavian vein thrombosis.…”
Section: Discussioncontrasting
confidence: 54%
“…There were no randomized controlled trials identified, and all 11 studies were comparative in design, 4 with concurrent controls 2-4,12 and 7 with historical controls. 5,6,[13][14][15][16][17] The methodological quality of the studies were limited, as none of the studies provided a clear description of the inclusion and exclusion criteria, and only 2 studies 4,13 reported that the groups were treated identically other than for the named intervention. Table I presents a summary of the methodological quality of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The age of the patients ranged from 26 2 to 93 years 15 (mean age 59.2 years and median age 58.6 years). The sample sizes in the trials were generally small and ranged from 28 2 to 285, 17 subjects, with 5 studies having unequal sample sizes between the comparison groups.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous papers have associated the establishment of an NST with improved clinical outcome and/or reduction in costS.25, 28,30,34,66,[70][71][72][73][74][75][76][77][78][79][80][81][82][83] The apparent implication of such data is that every hospital should have an NST. A difficulty with interpreting and implementing such a conclusion is the wide variability in already established NSTs, as discussed above.…”
Section: Data On the Efffects Of The Nstmentioning
confidence: 99%